2021
DOI: 10.1007/s12134-021-00889-z
|View full text |Cite
|
Sign up to set email alerts
|

Venezuelan Forced Migration to Peru During Sociopolitical Crisis: an Analysis of Perceived Social Support and Emotion Regulation Strategies

Abstract: While many studies have examined the impact of forced migration on Venezuelan migrants in Latin America, to date scholars have not examined the effect of certain coping mechanisms, namely social support and emotion regulation. Using data from 386 Venezuelan migrants living in Peru ( M = 20.22 years, SD = 1.33, 46.4% women), we investigated whether perceived social support from three different sources (family, friends, and significant other) correlated with emotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 91 publications
1
6
0
3
Order By: Relevance
“…Social support networks consist of family, friends, relatives, and a special person who can support individuals and reduce their stress [10]. Social support is too important, especially for refugees who migrated due to forced reasons such as war, political pressure, and fear of death [11]. Since refugees who had to migrate have left behind many material and moral losses.…”
Section: Introductionmentioning
confidence: 99%
“…Social support networks consist of family, friends, relatives, and a special person who can support individuals and reduce their stress [10]. Social support is too important, especially for refugees who migrated due to forced reasons such as war, political pressure, and fear of death [11]. Since refugees who had to migrate have left behind many material and moral losses.…”
Section: Introductionmentioning
confidence: 99%
“…On the three paths (i.e., social integration affecting health, social integration affecting social mentality, and social mentality affecting health), young male migrants were more affected than young female migrants. According to previous research, the level of social integration among young female migrants is lower than that of males, which is well explained by the low employment rate of females and the fact that they assume more family responsibilities, such as caring for children and the elderly ( Okumura et al, 2021 ). Chinese social culture has long been influenced by the traditional belief of “men outside home, women inside.” Traditional values, mores, and customs permeate daily life and convey a society’s positioning and expectations for women’s family roles through informal systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have been conducted to examine the relationship between social support, emotion regulation strategies, and mental health. A study in Peru demonstrated that social support was positively associated with cognitive reappraisal and negatively associated with expression suppression among Venezuelan migrants (Okumura et al, 2022). Further, a study in China demonstrated that social support was positively associated with cognitive reappraisal and negatively related to expression suppression; moreover, emotion regulation strategies played a mediating role between social support and anxiety and depression among breast cancer patients (Ma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%